Differential impact of fentanyl and morphine doses on ticagrelor-induced platelet inhibition in ST-segment elevation myocardial infarction: a subgroup analysis from the PERSEUS randomized trial - Garin, Dorian; Degrauwe, Sophie; Carbone, Federico; Musayeb, Yazan; Lauriers, Nathalie; Valgimigli, Marco; Iglesias, Juan F. (Frontiers in Cardiovascular Medicine, 2024)
Introduction Among patients with ST-segment elevation myocardial infarction (STEMI) treated with primary percutaneous coronary intervention (PCI), intravenous fentanyl does not enhance ticagrelor-induced platelet inhibition within 2 h compared to morphine. The impact of the total dose of fentanyl and morphine received on ticagrelor pharmacodynamic and pharmacokinetic responses in patients with STEMI remains however undetermined. Materials and methods We performed a post-hoc subanalysis of the prospective, open-label, single-center, randomized PERSEUS trial (NCT02531165) that compared treatment with intravenous fentanyl vs. morphine among symptomatic patients with STEMI treated with primary PCI after ticagrelor pretreatment. Patients from the same population as PERSEUS were further stratified according to the total dose of intravenous opioids received. The primary outcome was platelet reactivity using P2Y12 reaction units (PRU) at 2 h following administration of a loading dose (LD) of ticagrelor. Secondary outcomes were platelet reactivity and peak plasma levels of ticagrelor and AR-C124910XX, its active metabolite, at up to 12 h after ticagrelor LD administration. Generalized linear models for repeated measures were built to determine the relationship between raw and weight-weighted doses of fentanyl and morphine. Results 38 patients with STEMI were included between December 18, 2015, and June 22, 2017. Baseline clinical and procedural characteristics were similar between low- and high-dose opioid subgroups. At 2 h, there was a significant correlation between PRU and both raw [regression coefficient (B), 0.51; 95% confidence interval (CI), 0.02–0.99; p = 0.043] and weight-weighted (B, 0.54; 95% CI, 0.49–0.59; p < 0.001) doses of fentanyl, but not morphine. Median PRU at 2 h was significantly lower in patients receiving low, as compared to high, doses of fentanyl [147; interquartile range (IQR), 63–202; vs. 255; IQR, 183–274; p = 0.028], whereas no significant difference was found in those receiving morphine (217; IQR, 165–266; vs. 237; IQR, 165–269; p = 0.09). At 2 h, weight-weighted doses of fentanyl and morphine were significantly correlated to plasma levels of ticagrelor and AR-C124910XX. Conclusion In symptomatic patients with STEMI who underwent primary PCI after ticagrelor pretreatment and who received intravenous opioids, we found a dose-dependent relationship between the administration of intravenous fentanyl, but not morphine, and ticagrelor-induced platelet inhibition.